Exploring surface oxidation behavior of NiTi-V alloys - Acar, E.; Kok, M.; Qader, I. N. (Springer Heidelberg, 2020)
Non-isothermal oxidation behavior of Ni50Ti49.6V0.4 (at.%) and Ni50Ti46V4 (at.%) polycrystalline alloys was investigated through thermogravimetric analysis. Differential scanning calorimetry and scanning electron microscope were used to study the role of oxidations on the transformation temperatures and surface characteristics, respectively. It was revealed that the oxidation response of the alloys is very sensitive to the vanadium content and the oxidation temperature. The oxidation constant was linearly proportional to oxidation temperatures ranging between 850 and 1150 degrees C. It was found that the activation energies for oxidation decreased from 207.81 (-/+ 5.6) to 192.8 (-/+ 3.8) kJ/mol, while the vanadium content increased from 0.4 to 4%. The effects of chemical composition and temperature on the oxidation behavior were discussed. The surface of both alloys was covered by a titanium dioxide and nickel-enriched layer through the isothermal oxidation process. The grain size of the alloys was affected by the increasing oxidation temperature.
Keywords: Shape-Memory Alloys; Fe-Pt Alloys; Transformation Characteristics; Martensite-Transformation; Temperatures; Thermodynamics